Understanding of factors that enable health promoters in implementing health-promoting schools: a systematic review and narrative synthesis of qualitative evidence. - Tommy Tsz Man Hung; Vico Chung Lim Chiang; Angela Dawson; Regina Lai Tong Lee (PLoS ONE)
Health-promoting schools have been regarded as an important initiative in promoting child and adolescent health in school settings using the whole-school approach. Quantitative research has proved its effectiveness in various school-based programmes. However, few qualitative studies have been conducted to investigate the strategies used by health promoters to implement such initiatives. In this study, the researchers conducted a systematic review and narrative synthesis of the qualitative literature to identify important enablers assisting the implementation of health-promoting schools from the perspectives of health promoters. Five enablers have been identified from the review: (a) Following a framework/guideline to implement health-promoting schools; (b) Obtaining committed support and contributions from the school staff, school board management, government authorities, health agencies and other stakeholders; (c) Adopting a multidisciplinary, collaborative approach to implementing HPS; (d) Establishing professional networks and relationships; and (e) Continuing training and education in school health promotion. This highlights the importance of developing school health policies that meet local health needs, and socio-cultural characteristics that can foster mutual understanding between the health and education sectors so as to foster health promotion in children and adolescents.